Serum and urinary carnosinase-1 correlate with kidney function and inflammation - Zhang, Shiqi; Cui, Di; Tang, Mingna; Yang, Guang; Yard, Benito A.; Hu, Huaqing; Wu, Yonggui; Zhang, Qiu (Amino acids, 2023)
The carnosinase dipeptidase 1 (CNDP1) gene has been reported as a susceptibility locus for the development of diabetic kidney disease (DKD). While the (CTG)5 allele affords protection in the Caucasian population, we have previously shown that this allele is less frequently present in the Chinese population and therefore a protective role for the (CTG)5 allele is difficult to demonstrate. In the present study, we sought to assess if carnosinase-1 (CN-1) concentrations in serum and/or urine are associated with progression of DKD and to what extent CN-1 influences diabetes-associated inflammation. From a total of 622 individuals that enrolled in our study, 247 patients had type 2 diabetes without DKD, 165 patients had DKD and 210 subjects served as healthy controls. Uni- and multivariate regression analyses were performed to identify potential factors predicting urinary albumin creatinine ratio (UACR), estimated glomerular filtration rate (eGFR) and CN-1 concentration in serum and urine. The results indicated that serum CN-1 indeed correlated with eGFR (p = 0.001). In addition, urinary CN-1 associated with eGFR and tubular injury indicator: urinary cystatin C (Cys-C) and urinary retinol-binding protein (RBP). Interestingly, serum CN-1 also positively correlated with inflammatory indicators: neutrophils and lymphocytes. With regard to this, a STZ injected C57BL/6 mice model with surgically made skin wound was established for the generation of skin inflammation. This animal model further proved that the expression of CN-1 in liver and kidney increased remarkably in diabetic mice with skin wound as compared to those without. In conclusion, serum and urinary CN-1 significantly related to the surrogates of impaired renal function in diabetic patients; besides, CN-1 expression might also be associated with the process of inflammation.
Online veröffentlicht: 1. November 2022
Gesehen am 13.08.2024